The Search for Origin of Young Adoptees—A Clinical Study - Skandrani, Sara; Moro, Marie-Rose; Harf, Aurelie (Frontiers in Psychology, 2021)
In the current area of social media propagation, the adoptees' search for the birth family is increasingly reversed: more and more adopted adolescents are contacted directly by their birth parents, even if they did not search for them. This study explores the impact of these new forms of contact between adoptive family members and birth family members, through the qualitative analysis of clinical protocols of five adoptive families that sought counseling in a clinical setting devoted to international adoption. The interpretative phenomenological analysis revealed three themes. Two of them shared by the parents and their children: the feelings of anxiety and intrusion, as well as the feelings of guilt and debt. The last theme concerns only the parents: feelings of endangered family relations and can be divided into two sub-themes: feelings of threat by the birth family, feelings of an undermined parental role. Nevertheless, these new kinds of confrontations with the children’s origins bear a potential of renegotiating adoptive family relationships and positive effects on mutual feeling of filiation. Exploring the impact of the search of adoptees by the birth family enables professionals involved in adoption to improve preventive and supportive work in the adoption process.